Only Mom Can Save the World: Myths of Salvation and Destruction in Post-Apocalyptic Film - Millan, Katrina (Journal of the Motherhood Initiative for Research and Community Involvement, 2024)
A version of this paper was originally given at the Motherhood to Motherhoods: Ideologies of the ‘Feminine’ conference at Chapman University in April 2023. It presents a comparative textual analysis of two recent films dealing with mothering in the post-apocalypse—A Quiet Place (2018) and Bird Box (2018)—to examine a new maternal myth taking shape, which I call “only mom can save the world.” This work is broken into four sections. The first section confronts the irrefutability of white, heteronormative family structure in these works. The second section examines maternal subjectivity on screen. The third section deals with maternal regret, and the fourth section questions “mother love” as representative of a ubiquitous and unfailing survival strategy. I argue that although these films ostensibly present very different formulations of motherhood, they both ultimately work to affirm or re-establish white, middle-class heteronormative motherhood as the most vital form of emotional and social connection in the face of a collapsing world. Current myths of motherhood tell us that when deployed correctly, “mother love” has the power to shape the future. Considering contemporary anxieties surrounding ecological and economic disasters in our world, the need to examine these problematic myths takes on new weight and immediacy.